Idiosyncratic risk volatility: Stock price informativeness or price error? - Yuni Pristiwati Noer Widianingsih; Doddy Setiawan (Journal of Risk and Financial Management, 2022)
Research on idiosyncratic volatility in developing countries, particularly Indonesia, is scant. This study is the first to explain idiosyncratic concepts through an information environment approach and an examination of information asymmetry. This study aims to analyze the phenomenon of idiosyncratic risk in Indonesia, whether it is related to price informativeness or price error, by considering the information environment. We identified the information environment based on the liquidity levels and stock liquidity risk. Our research revealed the relationship between information asymmetry in the information environment and idiosyncratic volatility by using a sample of 499 companies listed on the Indonesia Stock Exchange during the period 2017-2019. One thousand, two hundred and twenty-nine (firm_year) observation data were obtained. The dependent variable was idiosyncratic volatility, and the independent variable used an information environment consisting of stock liquidity, liquidity risk, and information asymmetry. The findings of this study are expected to contribute to the literature on idiosyncratic volatility by showing how it can predict the development of the information environment, and how the latter is a consequence of information asymmetry. Moreover, this study should also complement views that are related to the concept of idiosyncratic volatility equivalent to price errors; this research has been carried out in previous studies.
Keywords: 650; liquidity risk; information asymmetry; idiosyncratic risk